ANALISIS PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DIMEDIASI OLEH KEPUASAN KERJA KARYAWAN PADA SP ALUMUNIUM DI YOGYAKARTA - Ita Kusumastuti; Novita ita Kurniawati; Deny Loka Satria; Dwi Wicaksono (Universitas Tidar, 2019)
The purpose of this study is to examine and analyze the influence of the work environment on employee performance which is mediated by the job satisfaction of employees of the Yogyakarta Alumunium SP. The research subjects were all employees in the production section of SP Yogyakarta Alumunium with 115 employees. This study included associative causal research using a quantitative approach. The sampling technique used is a saturated sample. Data was collected by questionnaires that had been tested using PLS SEM. The results of this study indicate that: the work environment positively and significantly affects employee performance and the environment positively and significantly affects employee performance which is mediated by employee job satisfaction. The implementation of the research findings is that the company must pay more attention to and improve the conditions of the work environment such as by overcoming noise and improving air circulation so that it will have an impact on increasing company performance accompanied by harmony among employees.